2010
DOI: 10.1200/jco.2009.27.0827
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Assessment of Cognitive Changes Associated With Adjuvant Treatment for Breast Cancer: Impact of Age and Cognitive Reserve

Abstract: These data demonstrated that age and pretreatment cognitive reserve were related to post-treatment decline in Processing Speed in women exposed to chemotherapy and that chemotherapy had a short-term impact on Verbal Ability. Exploratory analysis of the impact of tamoxifen suggests that this pattern of results may be due to a combination of chemotherapy and tamoxifen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

27
383
5
20

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 469 publications
(435 citation statements)
references
References 29 publications
27
383
5
20
Order By: Relevance
“…There is a growing body of evidence that cancer and its systemic treatments can have adverse effects on cognition in some, but not all, survivors of breast cancer 5, 6, 7. Older survivors may be especially vulnerable to cancer‐related decrements in cognitive function due to decreases in reserve 5.…”
Section: Introductionmentioning
confidence: 99%
“…There is a growing body of evidence that cancer and its systemic treatments can have adverse effects on cognition in some, but not all, survivors of breast cancer 5, 6, 7. Older survivors may be especially vulnerable to cancer‐related decrements in cognitive function due to decreases in reserve 5.…”
Section: Introductionmentioning
confidence: 99%
“…A growing body of evidence demonstrates that a subgroup of patients with BC have pretreatment cognitive deficits, [1][2][3][4][5] suggesting that aspects of cancer pathogenesis or host factors (potentially including variables related to BC surgery) cause cognitive changes or that there are common risk factors for the development of cancer and cognitive changes. 6 Prospective studies have shown cognitive changes differentially attributable to chemotherapy, radiation, and antiestrogen treatment, [7][8][9][10][11] highlighting the need for better understanding of potentially additive and dissociable effects of cancer treatments and the disease process on cognition in vulnerable individuals. 12 Structural and functional neuroimaging allow examination of the neural substrates of cancer-and treatment-related cognitive changes, which currently are poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…-Algunos dominios cognitivos pueden tener mayor propensión a sufrir deterioro (ver Tabla 1) (8,(13)(14)(15) -El déficit puede mantener una relación dosis-dependiente, presentando mayor riesgo las mujeres que reciben quimioterapia a dosis altas (16) . -La combinación de tratamientos antineoplásicos, por ejemplo quimioterapia más tamoxifeno, puede provocar alteraciones cognitivas más severas (10) .…”
Section: Estudios Longitudinalesunclassified